EDUKASI CARA PEMBUATAN “THE MILLE CREPE” SEBAGAI INOVASI BISNIS KULINER MODERN DI CABEAN KUNTI - Dhyni Triyas Pitaloka; Lilik Dea Tantri; Unik Latifah; Novian Alvina Siri; Unna Ria Safitri (KRIDA CENDEKIA, 2025)
The world of entrepreneurship continues to experience rapid development, especially in the food and beverage industry sector which has flexible characteristics and is responsive to market tastes. The culinary business, especially desserts, is one of the areas of interest to the younger generation because it offers opportunities for creativity, wide market potential, and a relatively low level of risk if managed properly. The Mille Crepe business is here as a response to the increasing consumer demand for sweet food products that are not only delicious, but also visually appealing and have high selling value. Mille crepe is a type of thin layered cake that is arranged in layers and filled with quality cream, presenting a smooth and luxurious taste. This study aims to examine aspects of business planning, market segmentation, operational strategies, and financial projections of this mille crepe business. The method used is a descriptive study with a case study approach based on real business proposals prepared by students. The results of the analysis show that with an initial capital of IDR 180.000 this business has the potential to generate a monthly gross profit of IDR 418.000. This business utilizes quality local ingredients and digital promotion strategies to reach the target market aged 15–35 years in Boyolali and its surroundings. With good management and continuous innovation, *The Mille Crepe* has promising prospects to develop as a leading culinary business.